Microstructural evolution in B-site Mg-substituted La0.9Sr0.1GaO3−δ oxide solid solutions - Azad, Abdul-Majeed; Er, Liew Foo (Elsevier Sequoia SALausanne, 2000)
Compositions with substitution both at A and B site of the host LaGaO3 system were synthesized via conventional solid-state reaction route. The substitution at A (La3+) site was fixed at 10 mole % Sr2+, while that at B (Ga3+) site was varied between 20 mole % and 50 mole % Mg2+. Cylindrical compacts were sintered using various temperature (T)-soak-time (t) profiles in the range 1200-1400°C and 2-72 h. X-ray analyses showed that up to 40 mole % MgO can go into the host lattice without resulting in new phases. Sintered bodies with higher amount of the dopant showed microstructures with mixed morphology, indicating that solid-solubility limit could have been exceeded. Microstructural examination also revealed that a soak-time of about 6 h at 1400°C was adequate to achieve benign microstructure in 20 mole % MgO-doped LaGaO3.